Possibility of Extracting Semantic Associates of Russian Verbs by the Instrument RusVectōrēs - M. K. Timofeeva (Научный диалог, 2018)
The paper presents the results of investigating distributional semantics’ potential in its realization in the form Web-service RusVectōrēs. The question about applying the service for studying semantics of Russian verbs is considered. The research urgency is caused by insufficient level of information about linguistic possibilities of distributional semantics in whole. The novelty of the research consist in the fact that the question about applying the instrument RusVectōrēs for investigating verb semantics is posed for the first time. Classification of semantic relations extracted by RusVectōrēs for Russian verbs is proposed. The analyzed data include two lists of entry verbs and the set of semantic associates for each verb; the integral set of considered semantic associates consists of 468 verbs. Special attention is paid to semantic relations that can be treated as lexical functions because this sort of relations appeared to be the most frequent for Russian verbs; the whole number of extracted lexical functions is equal to 28. It is shown that lexical functions that correspond to aspectual variants of verbs, to synonymic relations and conversion are the most frequent; hyponyms and co-hyponyms are the most frequent among semantic relations that differ from lexical functions; situational relations and actant relations are comparatively rare. Special attention is paid to the details that are important for applying the instruments of lexical functions to semantic relations extracted for verbs by the service RusVectōrēs.